Mutation of glucose-6-phosphate dehydrogenase deficiency in Chinese Han children in eastern Fujian. Issue 30 (July 2018) - Chen, Yao; Xiu, Wenlong; Dong, Yi; Wang, Jing; Zhao, Hong; Su, Yueqing; Zhou, Jinfu; Zeng, Yinglin; Li, Hua; Wo, Jingzhi; Lin, Feng; Zhang, Honghua; et al.
Abstract : Abstract: We aim to investigate the mutation types of glucose-6-phosphate dehydrogenase (G6PD) deficiency in Chinese Han children in eastern Fujian Province. A total of 904 Chinese Han neonates (male: 733 with positive G6PD deficiency and 28 with weakly positive deficiency; female: 73 with positive G6PD deficiency and 70 with weakly positive deficiency) received G6PD screening in our center from January 2014 to December 2016 were included in this study. Additionally, 904 age-matched normal Chinese Han individuals (male: 761; female: 143) were selected as control. Neonatal G6PD deficiency screening was performed through blood sample collection from the heels, using the commercial kits. Multicolor melting curve analysis (MMCA) method was used to determine the G6PD mutation type in the 904 cases. If it failed to detect mutations in the cases with abnormal enzyme activity, the polymerase chain reaction (PCR) and gene sequencing were used to determine the mutation sites. PCR and gene sequencing were used to determine the mutation sites in the 904 individuals with normal enzyme activity. Three most common mutation types in Chinese population were compared between Fujian and other provinces. Among the 904 neonates with abnormal G6PD enzyme activity, 17 mutation types were detected including 15 single point mutations and 7 complex mutations. Three most common mutation types were c.1376G > T, c.1388G > A, and c.95A > G accounted for 72.6% of the total mutations in eastern Fujian. The proportion of mutational types in G6PD and the degree of enzyme activity change in various mutational types were found in the neonates of Fujian Province. Our study may enrich the molecular diagnosis of G6PD deficiency meaning Fujian Province.